Join the conversation on IDNLearn.com and get the answers you seek from experts. Our Q&A platform offers reliable and thorough answers to ensure you have the information you need to succeed in any situation.

Rotate the axes to eliminate the [tex]$xy$[/tex]-term in the equation. Then write the equation in standard form. (Use [tex]$xp$[/tex] for [tex]$x^{\prime}$[/tex] and [tex][tex]$yp$[/tex][/tex] for [tex]$y^{\prime}$[/tex] in your answer. Rotate the coordinate axes through an angle [tex]$\theta$[/tex] with [tex]$0 \leq \theta \leq \frac{\pi}{2}$[/tex].)

[tex] xy + 4 = 0 [/tex]


Sagot :

To solve the problem of rotating the axes to eliminate the [tex]\(xy\)[/tex]-term in the equation [tex]\(xy + 4 = 0\)[/tex] and then writing the equation in standard form, we can follow a series of steps:

### Step 1: Identifying the Coefficients
First, we identify the coefficients [tex]\(a\)[/tex], [tex]\(b\)[/tex], [tex]\(c\)[/tex], and [tex]\(f\)[/tex] from the given equation:
[tex]\[ xy + 4 = 0 \][/tex]
This corresponds to:
[tex]\[ 0x^2 + xy + 0y^2 + 4 = 0 \][/tex]
From this, we see that:
[tex]\[ a = 0, \quad b = 1, \quad c = 0, \quad f = 4 \][/tex]

### Step 2: Finding the Angle of Rotation
To eliminate the [tex]\(xy\)[/tex]-term, we must find the angle [tex]\(\theta\)[/tex] that satisfies the following condition:
[tex]\[ \tan(2\theta) = \frac{b}{a - c} \][/tex]
Substituting our values:
[tex]\[ \tan(2\theta) = \frac{1}{0 - 0} = \frac{1}{0} \quad \text{(since } 0 - 0 = 0 \text{ and the division by zero leads to an infinite value)} \][/tex]
For [tex]\(\tan(2\theta)\)[/tex] to be infinite, [tex]\(2\theta = \frac{\pi}{2}\)[/tex]. Therefore:
[tex]\[ \theta = \frac{\pi}{4} \][/tex]

### Step 3: Calculating the New Coefficients in the Rotated Coordinate System
With [tex]\(\theta = \frac{\pi}{4}\)[/tex], we can find the new coefficients [tex]\(a'\)[/tex], [tex]\(b'\)[/tex], and [tex]\(c'\)[/tex]:
[tex]\[ a' = \frac{a + c}{2} + \frac{a - c}{2} \cos(2\theta) + \frac{b}{2} \sin(2\theta) \][/tex]
[tex]\[ c' = \frac{a + c}{2} - \frac{a - c}{2} \cos(2\theta) - \frac{b}{2} \sin(2\theta) \][/tex]
[tex]\[ b' = 0 \quad (\text{since the purpose of rotation is to eliminate the } xy \text{-term}) \][/tex]

Let's calculate each of these new coefficients:
[tex]\[ a' = \frac{0+0}{2} + \frac{0-0}{2} \cos(\frac{\pi}{2}) + \frac{1}{2} \sin(\frac{\pi}{2}) \][/tex]
Since [tex]\(\cos(\frac{\pi}{2}) = 0\)[/tex] and [tex]\(\sin(\frac{\pi}{2}) = 1\)[/tex]:
[tex]\[ a' = 0 + 0 + \frac{1}{2} \times 1 = \frac{1}{2} = 0.5 \][/tex]

[tex]\[ c' = \frac{0+0}{2} - \frac{0-0}{2} \cos(\frac{\pi}{2}) - \frac{1}{2} \sin(\frac{\pi}{2}) \][/tex]
[tex]\[ c' = 0 - 0 - \frac{1}{2} \times 1 = -\frac{1}{2} = -0.5 \][/tex]

Finally, the [tex]\(f\)[/tex] term remains unchanged:
[tex]\[ f' = 4 \][/tex]

### Step 4: Writing the Equation in Standard Form
Therefore, in the rotated coordinate system, the equation becomes:
[tex]\[ 0.5(x')^2 - 0.5(y')^2 + 4 = 0 \][/tex]

Hence, the transformed equation without the [tex]\(xy\)[/tex]-term is:
[tex]\[ 0.5(xp)^2 - 0.5(yp)^2 + 4 = 0 \][/tex]

This is the standard form of the equation after rotating through an angle of [tex]\(\theta = \frac{\pi}{4}\)[/tex].
Thank you for using this platform to share and learn. Keep asking and answering. We appreciate every contribution you make. IDNLearn.com has the solutions to your questions. Thanks for stopping by, and come back for more insightful information.